Pulmonary interstitial glycogenosis: an independent disease or morphological manifestation of the spectrum of interstitial lung diseases in infants? - O.L. Logvinova; M.A. Gonchar (Zaslavsky O.Yu., 2018)
The article presents a modern view on the problem of pulmonary interstitial glycogenosis, describes a typical clinical and morphological picture of the disease, and considers the disease etiology and the possibility of pulmonary interstitial glycogenosis to be as an independent form. The authors presented methods of modern diagnostics and treatment, as well as perspectives of studying this pathological condition in the world scientific community.